Monitoring and Managing Fiscal Risks in the East African Community - Mauro, Paolo (Departmental Papers; Departmental Paper, 2015)
This paper takes stock of the main fiscal risks facing the EAC partner countries. These include macroeconomic shocks, and specific risks, such as the financial performance of the public enterprises, large infrastructure projects, PPPs, and pension funds. In addition, weaknesses in the institutional framework are reviewed. This analysis highlights some of the largest risks and begins to give a sense of the potential magnitudes involved.